Substantial Impact of Later-Life Depression Among Community Older Adults on the Family Caregivers’ Burden in the Home Care Setting of Chiang Mai, Northern Thailand - Keisuke Shimizu; Myo Nyein Aung; Saiyud Moolphate; Thin Nyein Nyein Aung; Yuka Koyanagi; Siripen Supakankunti; Motoyuki Yuasa (Medicina)
Background and Objectives: Depression is a common geriatric problem globally. It is particularly burdensome in low- and middle-income countries, where care for older people mainly relies on the family in the absence of long-term care facilities. This study aimed to assess the level of caregivers’ burden among family caregivers who are taking care of older persons with depression in the home care setting within the communities of Chiang Mai, Northern Thailand. Materials and Methods: This cross-sectional study investigated 867 pairs of community-dwelling older adults and their family caregivers in Chiang Mai, Thailand. The depression of older people was screened using the 15-item Geriatric Depression Scale. The family caregivers’ burden and quality of life were measured using the Caregiver Burden Inventory (CBI) and the European Quality of Life (EQ) Five Dimension Five Level scales. The analysis applied was multivariable regression. Results: Two-thirds of the family caregivers were female. The mean age was 55.3 ± 13.8 years. The family caregivers caring for older persons with depression experienced significantly higher levels of burden in terms of the CBI total score (Coefficient: 10.60, 95% CI: 8.60, 12.60) and lower quality of life in terms of the EQ visual analogue scale (Coefficient: −5.52, 95% CI: −8.41, −2.62). They were more likely to take sick leave from their jobs (adj. OR 4.00, 95% CI: 1.73, 9.24) and more often to get sick (adjusted OR 7.26, 95% CI: 2.68, 19.64) than the caregivers of older adults without depression. Conclusions: Urgent interventions to prevent depression among older adults and systematic support to relieve family caregiver burden are necessary. The measures to relieve family caregiver burden include care capacity building, psychological support, respite care service, financial support, and other health promotion activities.